2015
DOI: 10.1007/s40069-015-0116-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anchorage Number on Behavior of Reinforced Concrete Beams Strengthened with Glass Fiber Plates

Abstract: Reinforced concrete beams with insufficient shear reinforcement were strengthened using glass fiber reinforced polymer (GFRP) plates. In the study, the effect of the number of bolts on the load capacity, energy dissipation, and stiffness of reinforced concrete beams were investigated by using anchor bolt of different numbers. Three strengthened with GFRP specimens, one flexural reference specimen designed in accordance to Regulation on Buildings Constructed in Disaster Areas rules, and one shear reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…U wraps are a type of traditional anchorage scheme that has been studied by many scholars [27,28]. CF anchors originally developed by the Shimizu Corporation in Japan offered a new way to anchor FRP sheets [29].…”
Section: Contribution Of Anchoring Schemesmentioning
confidence: 99%
“…U wraps are a type of traditional anchorage scheme that has been studied by many scholars [27,28]. CF anchors originally developed by the Shimizu Corporation in Japan offered a new way to anchor FRP sheets [29].…”
Section: Contribution Of Anchoring Schemesmentioning
confidence: 99%
“…The experimental findings showed that the contribution of the shear strength to the RC beams by these composite plates is limited due to the delamination of these plates along with the concrete cover. Kaya and Kankal (2015) studied the effect of anchorage bolt in shear-deficient RC beams strengthened using glass fibre–reinforced polymer (GFRP) plates, and the test result revealed that load-carrying capacity and ductility increases with increasing the number of anchorage bolts. Ramezanpur et al (2018) conducted an experimental test to see the effect of increasing the shear capacity of RC beam by developing the modified near-surface mounted technique using the GFRP bars which increased the shear capacity and ductility of RC beam.…”
Section: Introductionmentioning
confidence: 99%